Effects of the COVID-19 pandemic on the workload of caregivers: a case study of tabascan university lecturers who worked from home - Solana-Villanueva, Nélyda (2022)
This work analyzes the effect that telework had on the lives of the teachers of the Multidisciplinary Unit of the Universidad Juárez Autónoma de Tabasco (UJAT) in Mexico, during the confinement by COVID-19, mainly in care work in homes with 15 years or less children. The main argument in this study is whether this way of working affected female teachers more than male teachers. The results show that female teachers assumed the main role of care and domestic tasks, reconciling these demands teleworking from home, at the expense of reducing their sleep hours and having their physical and mental health affected (stress, depression, anxiety).